Effect of lidocaine spray during colposcopy-directed cervical biopsy: A randomized controlled trial - Tanyalak Wongluecha (2018)
© 2017 Japan Society of Obstetrics and Gynecology Aim: We aimed to examine the effect of lidocaine spray in reducing pain during colposcopy-directed cervical biopsy (CDB). Methods: Two hundred women with abnormal cervical screening test results and abnormal colposcopic findings that required a CDB during April to December 2015 were enrolled. The participants were randomly assigned into one of two groups. For group 1 (lidocaine group), 10% lidocaine spray was applied thoroughly to the ectocervix. For group 2, no anesthesia was given. The primary outcome of this study was the biopsy pain score. Results: Of the 200 women enrolled, 100 were randomly assigned to group 1 and 100 were in group 2. The baseline, biopsy, and postprocedure pain scores were comparable between the study groups. The mean difference between the biopsy and the baseline pain scores and the mean difference of the postprocedure pain scores from baseline were statistically significantly higher in the no-anesthesia group (group 2), P = 0.01 and P = 0.02, respectively. However, the degree of pain was minimal in both groups. There were no complications observed in any participants. Conclusion: Lidocaine spray reduces pain during colposcopy-directed cervical biopsy; however, the clinically meaningful effect of such a procedure cannot be demonstrated in this study.